(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
This study aims to provide technical platform for parameterized design female body model with different chest shapes. Initially, the characteristic parameters, curves and points of female chest shape were developed based on analysis of the features of female chest shapes. Then, these parameters were applied to make parameterized representation of the female chest characteristic points' coordinate; Parameters spline curve formulas were used to generate chest characteristic curves and the chest of parameterized modelling was realized. Furthermore, the parameterized modelling procedures of female chest were developed using development tools UG/Open, which could get different female chest shapes by inputting different parameter values.